A Post-Colonial Study of Magic Realism Blended in Superstitions in One Hundred Years of Solitude by Gabriel García Márquez - Bilal Hasan; Muhammad Nasir (Scholar Insight Journal, 2023)
Marquez Gabriel Garcia Marquez’s One Hundred Years of Solitude is a novel that is widely regarded as a masterpiece of the literary genre known as magical realism. The goal of showing regional politics is to make a statement about how inclined Latin American politics are to irrationality, ignorance, and tragic recurrences. But although some researchers dug into the novel regarding magical realism they missed the basic elements of superstitions that are dominating the novel as well as the magic realism of the novel. Marquez used superstitious magic realism in the novel and through the use of superstitious magic realism, Gabriel Garcia Marquez explores conflict, pain, and death in Colombia in the middle of the 1960s, a country that had seen two hundred thousand deaths due to political reasons. This superstitious magical touch combines supernatural components with everyday reality as well as superstitious life and brings the reader to Colombia, a country where superstitions, myths, omens, and tales coexist with technological advances and modernity. Along with other themes and events, these superstitions, myths, and real-life stories in the book record a significant section of Colombian history. In One Hundred Years of Solitude, Marquez uses superstitions to create a sense of mystery and wonder in the world he has created. The novel is set in the fictional town of Macondo, and its inhabitants are deeply superstitious.